2011
DOI: 10.2527/jas.2010-3574
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for mature weight in Angus cattle1

Abstract: The aim of this study was to estimate genetic parameters for BW of Angus cattle up to 5 yr of age and to discuss options for including mature weight (MW) in their genetic evaluation. Data were obtained from the American Angus Association. Only records from herds with at least 500 animals and with >10% of animals with BW at ≥ 2 yr of age were considered. Traits were weaning weight (WW, n = 81,525), yearling weight (YW, n = 62,721), and BW measured from 2 to 5 yr of age (MW2, n = 15,927; MW3, n = 12,404; MW4, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
(23 reference statements)
8
19
0
Order By: Relevance
“…In the animal breeding context, this means that selection on any of the evaluated traits will significantly impact the others and reinforces how important it is to apply a multivariate approach when working with growth traits. These results agree with those reported by Boligon (2008), Baldi Rey (2008) and Costa et al (2011). Additionally, these authors reported significantly higher direct additive genetic correlations between weaning weight and/or yearling weight and mature weights, implying that selection for weight at younger ages will lead to an increase in mature weight (Baldi Rey, 2008).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…In the animal breeding context, this means that selection on any of the evaluated traits will significantly impact the others and reinforces how important it is to apply a multivariate approach when working with growth traits. These results agree with those reported by Boligon (2008), Baldi Rey (2008) and Costa et al (2011). Additionally, these authors reported significantly higher direct additive genetic correlations between weaning weight and/or yearling weight and mature weights, implying that selection for weight at younger ages will lead to an increase in mature weight (Baldi Rey, 2008).…”
Section: Resultssupporting
confidence: 82%
“…Direct heritability estimates (h 2 ) were higher than those reported by Ferraz Filho et al (2002) and lower than those reported by Campêlo et al (2004) (Table 3). Boligon (2008), Baldi Rey (2008) and Costa et al (2011), who worked, respectively, with Nellore, Canchim and Angus breeds, reported, using a multi-trait model, higher h 2 than this study (>0.25) for weaning and yearling weights. Moderate and similar responses to selection are expected when selecting for weights at the four evaluated ages, since h 2 were similar and of average magnitude.…”
Section: Resultsmentioning
confidence: 44%
See 3 more Smart Citations